English-Speaking Children’s Interpretation of Disjunction in the Scope of ‘not every’ - Anna Notley; Rosalind Thornton; Stephen Crain (Biolinguistics, 2012)
This study examined 4- to 5-year-old English-speaking children’s inter-pretations of sentences containing negation, the universal quantifier, and disjunction. Disjunction is assigned two different meanings in such sentences depending on its position in surface syntax: in the subject phrase of ‘not every’ (e.g., not every passenger who ordered chicken or beef became ill), a disjunctive meaning is assigned to disjunction (e.g. at least one passenger who ordered chicken OR at least one passenger who ordered beef became ill); in the predicate phrase of ‘not every’ (e.g., not every passenger who became ill ordered chicken or beef), a conjunctive meaning is assigned (e.g., at least one passenger who became ill did not order chicken AND did not order beef). If children bring knowledge of combinatory logical principles to the task of language acquisition, then they should be sensitive to this asymmetry. We tested this prediction using a truth-value judgment task.